Expanding Brackets

Easy

Medium

Difficult

Q1) 3(2z -2) =
Q1) 5(3z -4) -6z -10 =
Q1) \((x + 2)(x + 5)\)
Q2) 2(2z + 8) =
Q2) 10(8w -2) +3w + 2 =
Q2) \((x -4)(x -4)\)
Q3) 4(3x -3) =
Q3) 8(5x + 8) +10x + 7 =
Q3) \((x -1)(x -1)\)
Q4) 4(2z -5) =
Q4) 5(7x + 2) +2x -6 =
Q4) \((x + 4)(x -2)\)
Q5) 9(2y + 2) =
Q5) 5(6y + 9) -3y -2 =
Q5) \((x -1)(x + 4)\)
Q6) 10(9x -2) =
Q6) 4(9y -2) +8y -6 =
Q6) \((x + 5)(x -1)\)
Q7) 2(3y + 2) =
Q7) 9(10x -3) +4x + 8 =
Q7) \((x -3)(x -4)\)
Q8) 4(7y -2) =
Q8) 8(7x + 8) -6x -2 =
Q8) \((x -3)(x -1)\)
Q9) 3(10y -2) =
Q9) 9(3z + 5) -10z -7 =
Q9) \((x + 3)(x + 1)\)
Q10) 7(10x + 4) =
Q10) 6(10y + 10) -5y + 2 =
Q10) \((x -3)(x + 4)\)